Microbial Interactions — Underexplored Links Between Public Health Relevant Bacteria and Protozoa in Coastal Environments - Eriksson, Karolina I. A.; Thelaus, Johanna; Andersson, Agneta; Ahlinder, Jon (Frontiers in Microbiology, 2022)
The co-existence of bacteria and protozoa in aquatic environments have led to the evolution of predation defense mechanisms by the bacteria. Some of the predation resistant bacteria (PRB) are also pathogenic to humans and other mammals. The links between PRB and protozoa in natural aquatic systems are poorly known but they are important in predicting outbreaks and determining long-term consequences of a contamination event. To elucidate co-occurrence patterns between PRB (16S) and bacterivorous protozoa (18S), we performed a field study in a coastal area in the northern Baltic Sea. Interactions between bacteria and protozoa were explored by using two complementary statistical tools. We found co-occurrence patterns between specific PRB and protozoa, such as Legionella and Ciliophora, but we also found that the interactions are genotype specific as for example Rickettsia. The PRB sequence diversity was larger in bays and freshwater inlets compared to offshore sites, indicating local adaptions. Considering the PRB diversity in the freshwater in combination with the large spring floods in the area, freshwater influxes should be considered a potential source of PRB in the coastal northern Baltic Sea. These findings are relevant for the knowledge of survival and dispersal of potential pathogens in the environment.